ВИЗНАЧЕННЯ МОДЕЛІ СЕНСОРНОЇ МЕРЕЖІ МЕТОДОМ СТРУКТУРНОЇ САМОІДЕНТИФІКАЦІЇ - Мєшков, Сергій Іванович; Хамула, Сергій Васильович; Пилипчук, Валентин Володимирович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
Define model of sensor networks by structural self-identification methods An important task when creating sensor networks is to optimize the parameters of the selected vector criteria. A self-use methods that are known to make it possible to carry out a systematic analysis and identification of complex objects, facilitating accurate long-term predictions about the development of the network settings that correspond to the range of services required.